Development of educational tool in modeling short term hydrothermal scheduling / Ahmad Ariff Shaberi - Shaberi, Ahmad Ariff (2011)
The usage of educational tools in helping the users to understand problems related to power engineering has become essential. By simulating the problems in software like MATLAB, the users can get a better picture on specific problems and the ways to solve it. In this thesis, a Graphical User Interface (GUI) has been developed using MATLAB® in modeling and solving short term hydrothermal scheduling on power system. The short term hydrothermal scheduling in this thesis involves 1 hydro plant and 1 thermal plant with their respective constraints. It is hoped that this graphical user interface (GUI) helps in improving the interest and understanding of the users on short term hydrothermal scheduling problem in more interactive and interesting way..